2016
DOI: 10.1155/2016/5970367
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Effects of Botanicals on Skeletal Muscle Health in Order to Prevent Sarcopenia

Abstract: We performed a systematic review to evaluate the evidence-based medicine regarding the main botanical extracts and their nutraceutical compounds correlated to skeletal muscle health in order to identify novel strategies that effectively attenuate skeletal muscle loss and enhance muscle function and to improve the quality of life of older subjects. This review contains all eligible studies from 2010 to 2015 and included 57 publications. We focused our attention on effects of botanical extracts on growth and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 67 publications
(73 reference statements)
0
33
0
Order By: Relevance
“…have been used to promote muscle health, strength and growth (Nkukwana et al, 2014). Similarly, scientific reviews on the effects of botanical extracts on muscle health (Rondanelli et al, 2016) describe their positive role in muscle growth and integrity.…”
Section: Effect Of Botanical Extracts On Amino Acid and Fatty Acid Prmentioning
confidence: 99%
See 2 more Smart Citations
“…have been used to promote muscle health, strength and growth (Nkukwana et al, 2014). Similarly, scientific reviews on the effects of botanical extracts on muscle health (Rondanelli et al, 2016) describe their positive role in muscle growth and integrity.…”
Section: Effect Of Botanical Extracts On Amino Acid and Fatty Acid Prmentioning
confidence: 99%
“…Muscle health and growth may be regulated by feeding curcumin, which was shown to improve broiler growth performance by regulating IGF-1 gene expression and enhancing the activity of antioxidant enzymes (Upadhaya et al, 2016;Alamdari et al, 2009). Recently, Rondanelli et al,(2016) described that botanical extracts may aid muscle regeneration and differentiation, reduce muscle atrophy, and demonstrated it has antiinflammatory and anti-fatigue properties, preventing muscle damage.…”
Section: Non-essential Amino Acid Profile Of Broiler Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…are known to have a significant level of activity in the prevention of muscle damage and pain resulting from inflammation and oxidative stress. More recent studies in animal models and in vitro demonstrate the antioxidative and anti-inflammatory roles of nutraceutical compounds including polyphenols, flavonoids, and phenolic acids through the modulation of the levels of proteins, plasma enzymes, cytokines, and receptors related to the immune response [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review reported a large number of herbal compounds with effects on skeletal muscles. 47 Some of the herbal compounds like curcumin from Curcuma longa , alkaloids and steroidal lactones from Withania somnifera , catechins from Camellia sinensis , proanthocyanidin of grape seeds, and gingerols and shogaols from Zingiber officinale showed modest effects on skeletal muscle in human studies. 47 However, the data supporting use of these supplements in people are limited with regards to efficacy, potential drug interactions and adverse effects and thus, recommendations for their use in sarcopenia is limited pending further research.…”
Section: Managementmentioning
confidence: 99%